Intertextuality transferred from literature to music: solutions adopted by different authors (Orfeu, 2024)
This article reviews the strategies adopted by various authors when applying intertextuality to music. Originating from literary theory, intertextuality examines the crossing of texts and their dialogue. In mu-sic, it addresses the relationships between musical realizations, whether notated or re-corded, complete or in excerpts. The aim of this article is to consolidate and differentiate these approaches. Initially, we present the main intertextual approaches in literature, distinguishing between post-structuralist and structuralist perspectives. Subsequently, we describe and compare their applications in music. Musical intertextuality encompas-ses subareas such as borrowing, influence, and Topic Theory. We also propose the su-barea of pragmatic intertextuality, with both analytical and compositional dimensions. We detail the particularities of these suba-reas and identify characteristics of the poie-tic, esthesic, and immanent processes from the semiotic perspective of Jean-Jacques Nattiez (1990; 2021). We conclude by dis-cussing recent trends in intermediality and adaptation studies. The article dedicates a more extensive section to the transtextuality of Gérard Genette (1997a; 2010), an author still underexplored in music.
Keywords: intertextuality; musical intertextuality; transtextuality; Gérard Genette